Influenza vaccines to control influenza-associated bacterial infection: Where do we stand? - Christopoulou, Ioanna (2014)
Influenza A virus is a pathogen that is feared for its capacity to cause pandemics. In this review, we illustrate the clinical evidence which support the theory that bacterial co-infection is a considerable risk factor for exacerbated disease during pandemic and seasonal influenza, including infection with influenza B viruses. We provide an overview of the multiple and diverse mechanisms that help explain how influenza creates an opportunity for replication of secondary bacterial infections. Influenza vaccines and pneumococcal vaccines are widely used and often in overlapping target groups. We summarize the evidence for a protective effect of influenza immunization against bacterial infections, and vice versa of pneumococcal vaccines against influenza-associated pneumonia and lethality. It is important that future implementation of broadly protective influenza vaccines also takes into account protection against secondary bacterial infection.